Understanding and supporting histopathology slide sorting. Issue 5 (4th May 2017) - Swindells, Colin; Tory, Melanie; Kincaid, Robert; Evans, Guy
ABSTRACT: Histopathology laboratories devote considerable time and effort to sorting tissue sample slides. We observed slide sorting in a typical urban hospital to understand the existing workflow and explore how it might be supported by an interactive computer support system. We observed 8.5 hours of slide sorting activity through a video camera mounted above a laboratory workbench. Through detailed video analysis, we characterised the process, examined which activities took the most time, and explored design considerations. We found that a very large proportion (23.5%) of the slide sorting time involved managing paper documents. We suggest that an interactive computer support system could automatically detect which slides are sorted into which folders and digitally list additional slides to include with these sets; this would support the workflow of technicians, while eliminating paper management and manual barcode reading operations, leading to time savings of approximately 30%. Additional recommendations for the design of such a support system include focusing on case management (e.g. how many slides belong to each case, whether a complete case will fit within the current folder, and which slides associated with a case are still missing), supporting recovery from disruptions, and enabling a flexible rather than a highly scripted workflow.